Pemanfaatan Teknologi Tepat Guna Dalam Meningkatkan Produksi Rengginang Di Kelurahan Sidodadi Kota Samarinda - Netty Maria Naibaho; Andi Lisnawati; Khusnul Khotimah; Rudito Rudito; Anis Syauqi; Mujibu Rahman; Tere Adi Susanti; Hamka Hamka; M. Yamin (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2020)
Rengginang is one of the traditional foods of the archipelago that has been consumed as a snack or main food since time immemorial. At the first rengginang is a food made from the rest of rice that does not run out, rather than being wasted in rice, it is processed into savory and crunchy food in the form of rengginang. Usually the processing is very simple, it is only dried by drying and frying and can be consumed immediately. Along with the time the tasty and crunchy food is very popular with consumers, so that the prestige of rengginang extends among the community and becomes one of the business opportunities for the culprit, especially the housewife, namely Mrs. Darmini. This science and technology for the community has a positive effect on partners and other business people that the importance of using simple technology is effective, thus increasing the production process of rice. The introduction and administration of a sealer is also very important to maintain the quality of the rengginang. Besides that, the need for legality of business such as P-IRT to ensure food security for consumers. This science and technology activity for the community is expected to continue as an effort to provide coaching and mentoring for micro-businesses that have the prospect of being able to survive and develop in the future